Effect of Catha edulis (khat) on pancreatic functions in streptozotocin-induced diabetes in male Sprague-Dawley rats - Alsalahi, Abdulsamad; Alshawsh, Mohammed Abdullah; Chik, Zamri; Mohamed, Zahurin (Japanese Association for Laboratory Animal Science, 2018)
People consume Catha edulis (khat) for its euphoric effect, and type 1 diabetics have claimed that khat could reduce elevated levels of blood sugar. However, khat has been suggested to provoke diabetes mellitus through destruction of pancreatic β-cells. This study investigated the effect of an ethanolic khat extract on pancreatic functions in type 1 diabetes (T1DM)-induced male Sprague-Dawley rats and to assess its in vitro cytotoxicity in rat pancreatic β-cells (RIN-14B). T1DM was induced in a total of 20 rats with a single intraperitoneal injection of 75 mg/kg of streptozotocin. The rats were distributed into four groups (n=5): the diabetic control, 8 IU insulin-treated, 200 mg/kg khat-treated, and 400 mg/kg khat-treated groups. Another 5 rats were included as a nondiabetic control. Body weight, fasting blood sugar, and caloric intake were recorded weekly. Four weeks after treatment, the rats were sacrificed, and blood was collected for insulin, lipid profile, total protein, amylase, and lipase analysis, while pancreases were harvested for histopathology. In vitro, khat exerted moderate cytotoxicity against RIN-14B cells after 24 and 48 h but demonstrated greater inhibition against RIN-14B cells after 72 h. Neither 200 mg/kg nor 400 mg/kg of khat produced any significant reduction in blood sugar; however, 200 mg/kg khat extract provoked more destruction of pancreatic β-cells as compared with the diabetic control. Ultimately, neither 200 mg/kg nor 400 mg/ kg of khat extract could produce a hypoglycemic effect in T1DM-induced rats. However, 200 mg/kg of khat caused greater destruction of pancreatic β-cells, implying that khat may cause a direct cytotoxic effect on pancreatic β-cells in vitro.